Social Sanction Ditinggian Janjang Against Violation of Traditional Law in Koto Gadang Preparation Nagari, Baso District, Agam Regency - Ulfia Hasanah; Latifah Alkhairiyah; Susilawati Susilawati; Sabrena Sukma (Faculty of Law, University of Mataram, 2021)
Based on research data, it is found that many teenagers in Indonesia have had sex before marriage. This behavior is not by the norms that apply in Indonesia, and of course, this deviant behavior will cause new problems in society. In Nagari Preparation Koto Gadang, West Sumatra, a social sanction was imposed on community members who violated Adat. This sanction is known as the social sanction